2021
DOI: 10.1210/jendso/bvab048.814
|View full text |Cite
|
Sign up to set email alerts
|

Severe, New-Onset Diabetes Mellitus Triggered by COVID-19 Infection Followed by Euglycemia Upon Recovery: A Case Report

Abstract: Background: New-onset diabetes mellitus (DM) and severe metabolic complications in association with COVID-19 has been reported in the literature. Studies indicate a bidirectional relationship between COVID-19 and DM. Not only does severe DM lead to an increased risk for COVID-19 complications, but COVID-19 infection itself may precipitate new-onset DM. Clinical Case: A 45-year-old male with no known past medical history and normal body mass index presented after being found unresponsive at home. One week prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies suggest that T1D or T1D-like diseases increased in prevalence during the pandemic. For example, a case series from Lincoln Hospital in New York, USA found T1D and T1D-like hyperglycemia to increase during the pandemic [ 4 ], as have case reports from New Jersey, USA [ 5 ], Peru [ 6 ], and France [ 34 ]. Of note, a number of these have demonstrated that COVID-associated DM is not always persistent across time, but occasionally dissipates weeks and months after the SARS-CoV-2 infection subsides [ 4 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that T1D or T1D-like diseases increased in prevalence during the pandemic. For example, a case series from Lincoln Hospital in New York, USA found T1D and T1D-like hyperglycemia to increase during the pandemic [ 4 ], as have case reports from New Jersey, USA [ 5 ], Peru [ 6 ], and France [ 34 ]. Of note, a number of these have demonstrated that COVID-associated DM is not always persistent across time, but occasionally dissipates weeks and months after the SARS-CoV-2 infection subsides [ 4 , 34 ].…”
Section: Discussionmentioning
confidence: 99%